Impact of pesticide outsourcing services on farmers’ low-carbon production behavior - Yang, Yifan; Yu, Yanli; Li, Ruining; Jiang, Debang (Frontiers in Environmental Science, 2023)
Introduction: Promoting low-carbon development in agriculture is crucial for achieving agricultural modernization. One practical issue worth studying is whether outsourcing services can encourage farmers to adopt low-carbon production practices. This study analyzes the impact of pesticide outsourcing services on the low-carbon production behavior of farmers to provide China with practical recommendations. Methods: This empirical study investigates the impact of pesticide outsourcing services on farmers’ low-carbon production behavior using survey data from 450 rice growers in the Ningxia and Shaanxi provinces by endogenous switching regressions (ESR) model. Results and Discussion: Results showed that 1) outsourcing services have a significant negative impact on farmers’ manual weeding behavior, leading to a reduction in the frequency of manual weeding; 2) outsourcing services have a significant positive impact on farmers’ herbicide application behavior. In other words, participation in outsourcing leads to excessive pesticide application; 3) outsourcing services do not support a green and low-carbon production model where manual weeding replaces herbicide application. Due to the imperfect development of the outsourcing market in China, especially in the northwest region, the construction of outsourcing service system is lagging, and it is difficult for non-professional outsourcing services to play a driving role in green and low-carbon production for farmers, who will often choose the lower-cost mechanical application for maximum profit. The policy implication of this study is the need for a comprehensive and objective understanding of the impact and role of pesticide outsourcing services on farmers’ low-carbon production behavior. This understanding can help improve the market, policy, and other external environments for farmers to participate in outsourcing, ultimately promoting the sustainable development of green and low-carbon agriculture. This paper adds to the discussion of pesticide outsourcing services and farmers’ low-carbon production by drawing different conclusions from previous studies, providing a fresh foundation for policy-making.